2016
DOI: 10.1186/s13068-016-0464-7
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally friendly and productive process for bioethanol production from potato waste

Abstract: BackgroundChina is the largest sweet potato producer and exporter in the world. Sweet potato residues (SPRs) separated after extracting starch account for more than 10 % of the total dry matter of sweet potatoes. In China, more than 2 million tons of SPRs cannot be utilized, and the unutilized SPRs are perishable and result in environmental pollution. Thus, an environmentally friendly and highly efficient process for bioethanol production from SPRs should be developed.ResultsThe swelling behaviour of cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…During this process, sugars are converted into ethanol, energy, cellular biomass, CO 2 and other byproducts by yeast cells. These sugars may come from different feedstocks and crop wastes 16, 17. In Brazil, the main feedstock is sugarcane while the United States of America (USA) produces ethanol from corn 16, 18.…”
Section: Introductionmentioning
confidence: 99%
“…During this process, sugars are converted into ethanol, energy, cellular biomass, CO 2 and other byproducts by yeast cells. These sugars may come from different feedstocks and crop wastes 16, 17. In Brazil, the main feedstock is sugarcane while the United States of America (USA) produces ethanol from corn 16, 18.…”
Section: Introductionmentioning
confidence: 99%
“…Root crops, such as sweetpotato and cassava have been proposed as substitutes for corn-based ethanol production considering their high ratio of output (bioethanol produced from such crops) to input (estimates of fertilizer, water, and pesticide) (Ziska et al, 2009). Several studies have been reported to have developed efficient biofuel extraction methods from sweetpotatoes and their residues in the form of hydrogen, ethanol, and methane Lay et al, 2012;Kobayashi et al, 2014;Wang F. et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Different conditions like fresh feed rate, liquid recycling etc. optimization was done to find the best possible conditions [11]. The study done utilized RSM and central composite face centered design to find best possible condition to maximize ethanol production in batch fermentation from sugarcane molasses using Saccharomyces cerevisiae Y-39 [12].…”
Section: Literature Reviewmentioning
confidence: 99%